Kajian Filosofis berparadigma Positivisme : Pelaksanaan Corporate Social Responsibility sebagai Kewajiban menurut Undang-Undang dalam Mewujudkan Good Corporate Governance - Peni Rinda Listyawati (UNISSULA, 2016)
Positivism point of view can be declared as valid if it is specified by the institution or the competent authority and based on the rule of higher and not hung on moral values. That legal norm as we know is the Act.Law is a manifestation of the will of the government or can be said as way to arrange something in order to achieve the objectives as it is mentioned in the political law contained in the preamble or a general description. Furthermore, the Government has enacted the Corporate Law which is found in Article 74. This article set of Social and Environmental Responsibility (Corporate Social Responsibility). The fundamental question is why CSR including ethical conduct/ morality of a company, is included into law which must be implemented by the company? This question can not be answered by jurisprudence that has a limited scope. Since it only study about the norms or rules (laws). Moreover, when this condition occurs, it will go to be the object of philosophical discussion.Article 74 of Law No. 40 of 2007 has demonstrated that moral action can be increased its power to become law. Social and environmental responsibility norm become a legal obligation. It rules policy to create Acts and give sanction. The basic value is that the company in business activity has caused negative impacts resulting in losses for the community. In addition, CSR is responsible on the principle of sustainable development. Thereby, by implementing Corporate Social Responsibility properly, it will create Good Corporate Governance (GCG)